A case of Acute myeloid leukemia complicated by post COVID-19 multi-system inflammatory syndrome-children - Nalla Anuraag Reddy; Alex Tom; Harsha Prasada Lashkari (Elsevier, 2022)
Corona Virus disease 2019 (COVID-19) pandemic has presented a huge challenge to the health care system in terms of magnitude of cases and to pediatric oncology units with varied clinical presentations. Acute myeloid leukemia(AML) is a rare heterogenous cancer of childhood with an induction mortality around 15% in our country due to neutropenic sepsis. Multisystem inflammatory syndrome in children(MIS-C) is an hyperinflammatory syndrome seen 4-6 weeks after COVID-19 infection. COVID infection in some of these children would have gone unnoticed. Here we report a two year eight months old boy diagnosed with AML on induction chemotherapy developed post COVID MIS-C.